(untitled) - Heyhoe, Kate (Hoboken, 2004)
Harvesting the Dream is the rare story of a large and successful business that remains family owned and continues to operate on the basis of professional and personal integrity. You'll follow the Trinchero family from their common origins in a New York flooded with immigrant families like themselves, to their uncommon rise to success, to the present business challenges they face in the new Napa Valley. Their story brings the American dream to life-and underscores the reality that hard work and the willingness to defy well-rooted conventions are still the building blocks of business success.
Keywords: Sutter home winery,Wine and wine making,Wineries; History,History,History; California,Napa valley,California,Napa valley